Accurate Control of Multishelled Co3O4 Hollow Microspheres as High‐Performance Anode Materials in Lithium‐Ion Batteries1. Issue 25 (6th May 2013) - Wang, Jiangyan; Yang, Nailiang; Tang, Hongjie; Dong, Zhenghong; Jin, Quan; Yang, Mei; Kisailus, David; Zhao, Huijun; Tang, Zhiyong; Wang, Dan
<x xml:space="preserve">Abstract</x> More than just an empty shell: Multishelled Co3O4 microspheres were synthesized as anode materials for lithium‐ion batteries in high yield and purity. As their porous hollow multishell structure guarantees a shorter Li+ diffusion length and sufficient void space to buffer the volume expansion, their rate capacity, cycling performance, and specific capacity were excellent (1615.8 mA h g−1 in the 30th cycle for triple‐shelled Co3O4; see graph).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>